Personality psychology horizons. Review of Henryk Gasiul's book 'Psychology of Personality: Currents - Theories - Concepts' - Zeidler, Włodzisław (Studia Psychologica: Theoria et praxis, 2020)
Review of Henryk Gasiul's book 'Psychology of Personality: Currents - Theories - Concepts'